Analisis Yuridis terhadap Keabsahan Klausul Arbitrase dalam Kontrak BUMN Indonesia Berdasarkan Batas Kewenangan Negara dan Prinsip Imunitas Negara : Penelitian - Bernard Sindak Pangihutan Lumban Siantar; Ivan Nurchalik; Exal Sinaga; Hammamtio; Diani Sadiawati (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
The fundamental restructuring of Indonesian State-Owned Enterprises (SOEs) in 2025–2026 through the BPI Danantara super-holding has generated acute doctrinal tension between private commercial autonomy and public sovereign immunity claims. Employing a doctrinal legal research methodology with statutory, conceptual, case, and comparative approaches, this study analyzes the juridical validity of arbitration clauses following the Constitutional Court Decision No. 100/PUU-XXII/2024 and formulates transnational legal protections for third parties. The findings indicate that while arbitration clauses remain valid under the acta jure gestionis doctrine, the newly adopted pure territoriality principle subjects arbitral awards to domestic public policy oversight. Consequently, these clauses are highly vulnerable to nullification (void ab initio) if contaminated by détournement de pouvoir. Furthermore, the enforcement phase frequently reaches an impasse due to the weaponization of Article 50 of the State Treasury Law as a tactical sovereign shield. To resolve this deadlock, this study recommends a preventive framework by explicitly incorporating digital and financial asset immunity waivers in preliminary contracts. Repressively, disputes must be elevated to transnational investment forums (ICSID) by invoking the Alter Ego doctrine to pierce the state's corporate veil and strictly enforce State Responsibility.